The Process of Forming the Character of The Insan Kamil Through the Seven Habits of Great Indonesian Children Program at SDIT Permata Hati Banjarnegara - Siti Ngarofah; Sri Haryanto; Nurul Mubin Haryanto; Muhamad Yusuf Amin Nugroho; Nia Natasya; Ahmad Najih Musoffa Fuadi; Arim Irsyadulloh Albin Jaya; Dyah Ayu Fitriana (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2024)
Kamil refers to the ideal human being who possesses noble character and commendable morals in accordance with Islamic teachings. Achieving this ideal, however, requires systematic educational strategies. One such approach is the Seven Habits of Great Indonesian Children program, which has been integrated as a core activity at SDIT Permata Hati Banjarnegara. Through this program, the school seeks to cultivate students’ character holistically so that they develop into individuals who embody the values of insan kamil.This study employed a descriptive qualitative design using phenomenological, pedagogical, and psychological approaches. Data were collected from teachers, homeroom teachers, the principal, students, and parents through observation, interviews, and documentation. Data analysis involved reduction, presentation, and conclusion drawing, while data validity was ensured through triangulation and reference checks.The findings indicate that the implementation of the Seven Habits program includes waking up early, worshipping, exercising, eating healthy and nutritious food, loving learning, engaging in social activities, and going to bed early. These practices foster key character traits such as religiosity, discipline, honesty, care, responsibility, independence, intelligence, and cooperation. Collectively, these values integrate spiritual, intellectual, emotional, and social dimensions, forming the foundation of a complete and noble human being (insan kamil).